Indonesian Celebrities on YouTube: An Analysis Using Bourdieu’s Perspective - Sihombing, Lambok Hermanto; S, Jonathan William; Lestari, Puji (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
Numerous Indonesian celebrities moving to YouTube have dominated the viewership and trending segments. The researchers chose Deddy Corbuzier, Baim Wong, Raffi Ahmad, and Nagita Slavina as they are celebrities who transitioned to YouTube and achieved success after only a few years of its existence. Using Bourdieu's social capital theory, the researchers identified celebrities' capitals that give them an advantage when transitioning to YouTube. Capitals resulted in dominance and elevated celebrities to celebrity status. According to Bourdieu, cultural capital may play a significant role in pursuing power and position within a community. This condition, we believe, exists as a result of the relationship between celebrities and their fans. Celebrities attempt to attract fans through the use of YouTube in order to achieve power. As a result, YouTube celebrities view these opportunities as business opportunities that eventually lead to financial success.